RESEARCH OF ULTRASONIC MATERIAL REMOVAL MECHANISM AT HYBRID ELECTROCHEMICAL FINISHING (Nonconventional Technologies Review, 2025)
This paper presents the current state of the art of ultrasonic aided electrochemical polishing, which involves anodic dissolving of the machined material predominantly around the microgeometry peaks of the machined surface, ultrasonic depassivation of the neutral layer deposited on the machined surface and roughness (Ra) decrease by ultrasonic removal of the microgeometry protrusions. Numerical simulations of ultrasonic concentrators integrating different tool sizes and different thicknesses of the electrical insulating layer to achieve the resonance condition are performed. Numerical simulations are also developed on the process of material removal and depassivation when machining a stainless steel. The results of the numerical simulations are validated by experimental results obtained, which show the correct operation of the ultrasonic chains and finding an optimum value of ultrasonic power (pressure) for maximum Ra decrease.
Keywords: electrochemical polishing; ultrasonic; numerical simulation